Media ethics goes to the movies - Good, Howard, 1951- (Praeger, 2002)
Certain films seem to encapsulate perfectly the often abstract ethical situations that confront the media, from truth-telling and sensationalism to corporate control and social responsibility. Using these movies--including Ace in the Hole, All the President's Men, Network, and Twelve Angry Men--as texts, authors Howard Good and Michael Dillon demonstrate that, when properly framed and contextualized, movies can be a powerful lens through which to examine media practices.